Antimicrobial prescribing in SARS-CoV-2. (2nd April 2021) - Robertson, Deborah
Abstract : Deborah Robertson provides an overview of recently published articles that may be of interest to non-medical prescribers. Should you wish to look at any of the papers in more detail, a full reference is provided